Cost-effectiveness of self-management of blood pressure in hypertensive patients over 70 years with suboptimal control and established cardiovascular disease or additional cardiovascular risk diseases (TASMIN-SR). (29th August 2020) - Penaloza-Ramos, Maria Cristina; Jowett, Sue; Mant, Jonathan; Schwartz, Claire; Bray, Emma P; Sayeed Haque, M; Richard Hobbs, FD; Little, Paul; Bryan, Stirling; Williams, Bryan; McManus, Richard J
Abstract: Background: A previous economic analysis of self-management, that is, self-monitoring with self-titration of antihypertensive medication evaluated cost-effectiveness among patients with uncomplicated hypertension. This study considered cost-effectiveness of self-management in those with raised blood pressure plus diabetes, chronic kidney disease and/or previous cardiovascular disease. Design and methods: A Markov model-based economic evaluation was undertaken to estimate the long-term cost-effectiveness of self-management of blood pressure in a cohort of 70-year-old 'high risk' patients, compared with usual care. The model used the results of the TASMIN-SR trial. A cost–utility analysis was undertaken from a UK health and social care perspective, taking into account lifetime costs of treatment, cardiovascular events and quality adjusted life years. A subgroup analysis ran the model separately for men and women. Deterministic sensitivity analyses examined the effect of different time horizons and reduced effectiveness of self-management. Results: Base-case results indicated that self-management was cost-effective compared with usual care, resulting in more quality adjusted life years (0.21) and cost savings (–£830) per patient. There was a 99% chance of the intervention being cost-effective at a willingness to pay threshold of £20, 000 per quality adjusted life year gained. Similar results were found for separate cohorts of men and women. The results were robust to sensitivity analyses, provided that the blood pressure lowering effect of self-management was maintained for more than a year. Conclusion: Self-management of blood pressure in high-risk people with poorly controlled hypertension not only reduces blood pressure, compared with usual care, but also represents a cost-effective use of healthcare resources.